Characterization of sensory and motor dysfunction and morphological alterations in late stages of type 2 diabetic mice - Tian, Ting; Li, Haofeng; Zhang, Sensen; Yang, Maojun (Frontiers in Endocrinology, 2024)
Diabetic neuropathy is the most common complication of diabetes and lacks effective treatments.Although sensory dysfunction during the early stages of diabetes has been extensively studied in various animal models, the functional and morphological alterations in sensory and motor systems during late stages of diabetes remain largely unexplored. In the current work, we examined the influence of diabetes on sensory and motor function as well as morphological changes in late stages of diabetes. The obese diabetic Lepr db/db mice (db/db) were used for behavioral assessments and subsequent morphological examinations. The db/db mice exhibited severe sensory and motor behavioral defects at the age of 32 weeks, including significantly higher mechanical withdrawal threshold and thermal latency of hindpaws compared with age-matched nondiabetic control animals. The impaired response to noxious stimuli was mainly associated with the remarkable loss of epidermal sensory fibers, particularly CGRP-positive nociceptive fibers. Unexpectedly, the area of CGRP-positive terminals in the spinal dorsal horn was dramatically increased in diabetic mice, which was presumably associated with microglial activation. In addition, the db/db mice showed significantly more foot slips and took longer time during the beam-walking examination compared with controls. Meanwhile, the running duration in the rotarod test was markedly reduced in db/db mice. The observed sensorimotor deficits and motor dysfunction were largely attributed to abnormal sensory feedback and muscle atrophy as well as attenuated neuromuscular transmission in aged diabetic mice. Morphological analysis of neuromuscular junctions (NMJs) demonstrated partial denervation of NMJs and obvious fragmentation of acetylcholine receptors (AChRs). Intrafusal muscle atrophy and abnormal muscle spindle innervation were also detected in db/db mice. Additionally, the number of VGLUT1-positive excitatory boutons on motor neurons was profoundly increased in aged diabetic mice as compared to controls.Nevertheless, inhibitory synaptic inputs onto motor neurons were similar between the two groups. This excitation-inhibition imbalance in synaptic transmission might be implicated in the disturbed locomotion. Collectively, these results suggest that severe sensory and motor deficits are present in late stages of diabetes. This study contributes to our understanding of mechanisms underlying neurological dysfunction during diabetes progression and helps to identify novel therapeutic interventions for patients with diabetic neuropathy.